Pengaruh Peranan dan Kegiatan Kelompok Tani terhadap Keberlanjutan Padi Varietas Lokal di Kabupaten Tana Toraja - Pakiding, Fani Lande; Zain, Majdah M.; M., Musdalifah; Ibrahim, Helda (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of farmer group roles and activities on the sustainability of local rice varieties in Tana Toraja Regency. The research is motivated by various challenges that threaten the preservation of local rice varieties, including agricultural modernization, climate change, and weak institutional support, all of which contribute to the degradation of local rice germplasm that holds ecological, socio-cultural, and economic significance. A descriptive quantitative approach supported by qualitative insights was employed in this study. A total of 71 respondents were selected through a saturated sampling technique, representing active members of three farmer groups: Burau Tarra in South Sangalla District, as well as Bokko and Tagari in North Sangalla District. Data were collected through Likert-scale questionnaires, interviews, observations, and documentation. The analysis was conducted using descriptive statistics and Pearson correlation tests. The findings indicate that the role of farmer groups is categorized as high, reflecting institutional effectiveness in enhancing member capacity, strengthening group solidarity, and fostering awareness of local variety conservation. Farmer group activities—including local seed conservation, technical training, institutional deliberation, socio-cultural agricultural activities, and productive economic initiatives—also fall within the high category. Pearson correlation analysis revealed a very strong and significant relationship between farmer group activities and the sustainability of local rice varieties (r = 0.771; p < 0.01). Overall, the sustainability of local rice varieties in Tana Toraja is classified as high, encompassing ecological, socio-cultural, and economic dimensions.